2010
DOI: 10.1111/j.1365-2702.2010.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various interventions to newborns on pain and duration of crying

Abstract: Health care personnel should perform painful interventions to the newborns while the babies are held by their mothers and during the procedure use of sucrose should be the primary choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Audible and inaudible crying responses to heel stick pain have been successfully tested in experimental studies examining the effects of kangaroo care 32 and sucrose on reducing infant pain. 33 Further studies using a psychoacoustic status, and therapeutic interventions, make infant pain assessment even more complicated.…”
Section: Behavioral Pain Responsesmentioning
confidence: 99%
“…Audible and inaudible crying responses to heel stick pain have been successfully tested in experimental studies examining the effects of kangaroo care 32 and sucrose on reducing infant pain. 33 Further studies using a psychoacoustic status, and therapeutic interventions, make infant pain assessment even more complicated.…”
Section: Behavioral Pain Responsesmentioning
confidence: 99%
“…We retrieved 44 articles where NI underwent PMP [10–53]. NI enrolled as controls received analgesia only in eight studies (14.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies by Curtis et al (2007) and Yilmaz and Arikan (2011) concluded that the joint use of sucrose and a pacifier were proven to be most effective. From these studies it is clear that the natural action of sucking for a neonate may result in a comforting response and when combined with sucrose, there seems to be an analgesic effect.…”
Section: The Combined Use Of Sucrose With Other Strategiesmentioning
confidence: 98%